MEDIA E-LEARNING STORYMAPS BERBANTUAN CROSSWORD PUZZLE MATERI KEKAYAAN ALAM YANG ADA DI INDONESIA UNTUK MENINGKATKAN VISUAL SPASIAL SISWA KELAS V SEKOLAH DASAR - Adina, Atik; Alfi, Cindya; Fatih, Mohamad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aim of this research is to produce a product that is used as learning media in Class V, namely e-laening storymaps assisted by crossword puzzle to improve students’ spatial visuals. This type of development uses the ASSURE model which includes analyze learnes,state objectivitas,select methods, media, and materials,utilize materials,require learnes participation,and evaluate and revise. The instrument used was a questionnaire. Producy validity tests were obtained from media experts, material experts and language experts. Material expert assessment reached 975. Media expert results reached 91%. Meanwhile for linguists it reaches 88%. Next, the feasibility test for e-learning storymaps by crossword puzzle is based on the results of the teacher response questionnaire. The results of the teacher response questionnaire 97,5% in the very appropriate category. Based on research on e-learning media, storymaps assistes by crossword puzzle can help improve students’ spatial visuals. These results are based on an average NGain score of 0,81 in the high category